Putting the Margins at the Centre: At the Edges of Protest in Morocco and Egypt - De Smet, Brecht; El Kahlaoui, Soraya (PARTECIPAZIONE E CONFLITTO, 2021)
Almost ten years have passed since the Arab uprisings of 2011 turned the social-political equilibrium of the Middle East and North Africa (MENA) region upside down. Despite successful counter-revolutionary policies, protests continue to challenge the status quo. The main difference with the 2011 is that current and ongoing political and social protests are less "visible" as they happen at the "margins" of society. This paper investigates the role of marginality and marginalisation in the cycle of protests and the dynamic of revolution and counter-revolution in the MENA region. The continuous eruption of social contestations in the rural and urban margins of North Africa forces us to reconsider previous academic analyses which understood the so-called "Arab Spring" as a predominantly urban youth movement, principally from a middle-class background. Protests at the margins not only constitute the hidden history of revolts of 2011, they also continue these revolts in a less visible, less concentrated, and less articulated manner. Putting the margins at the centre of analysis allows us to conceive of a cycle of protest not only in diachronic terms, as a temporal ebb and flow of contestation, but also a socio-spatial process of converging and refracting protests – from the margins to the centre and back again. We take a closer look at events in Egypt and Morocco. For the Egyptian case we investigate rural and urban protests against the new Law on Building Violations. Through the lens of marginalisation, we are able to reveal the contours of a socio-spatial hierarchy of protests, which has been shaping social movements in Egypt long before 2011. The second case deals with Morocco and presents a counter-story of the post-2011 democratic transition which has led, to everyone’s surprise, to the uprising of the Hirak du Rif and Jerada. This counter-story traces the reconfiguration of power relations in society, thanks to mobilisations that took place often underground and at the margins.